Analysis of heavy metals fixation and associated energy consumption during sewage sludge combustion: Bench scale and pilot test. (20th August 2019) - Chen, Tao; Lei, Chang; Yan, Bo; Li, Li-li
Abstract: The combustion is an effective way of sewage sludge treatment and provides an attractive source of energy. However, the heavy metals (HMs) volatilization and the energy demand are restrictive factors for sewage sludge combustion. This study focused on the heavy metals fixation with the sorbents addition and the energy balance of sludge combustion using the bench scale and pilot tests. The proximate and the combustion characteristic analysis showed that the volatile component burning played a dominant role during the combustion of the sludge, but the reaction mechanisms for their combustion steps were different. Bench-scale tests indicated that with 6.25% kaolin addition, temperature of 900 °C, and residence time of 20 min, the fixation ratios of Cu, Pb, Ni, Cd, Cr, and Zn were reached 94.60%, 90.69%, 93.75%, 90.71%, 92.21%, and 96.53%, respectively. Long-term pilot tests demonstrated that the energy consumption for the combustion of one ton dehydrated sludge could be as low as 62 kW h with a 10-m long electric heating rotary kiln. Furthermore, the escaped Pb, Cd, Cr, Cu, Ni, and Mn were only 2.12 g, 0.12 g, 0.86 g, 33.90 g, 1.61 g, and 66.67 g, respectively, per ton dried sludge. This study can provide an environmentally friendly and economical way of treating sludge. Graphical abstract: Image 1 Highlights: The burning of the volatile component of sewage sludge plays a dominant role during sludge combustion. The trapping of heavy metals is increased with a 6.25% kaolin addition. Total heavy metal emissions were approximately 99 g per ton dried sludge. The energy consumed for the combustion of one ton dehydrated sludge was 62 kW. h